Anteseden dari E-Commerce User Satisfaction - Reva Vebria Oliviana (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to analyze the effect of quality system, information system, service and product quality, and delivery service have a positive effect on e-commerce user satisfaction. The sampling method used is purposive sampling with a sample 200 respondents who are users of e-commerce applications such as Shopee. The results of this study statethere is a positive effect on the quality of system, information, delivery service, and services on e-commerce user satisfaction, and product quality have no effect with e-commerce user satisfaction.